2012
DOI: 10.1007/s12160-012-9413-2
|View full text |Cite
|
Sign up to set email alerts
|

School Sport Participation Under Two School Sport Policies: Comparisons by Race/Ethnicity, Gender, and Socioeconomic Status

Abstract: Background School-based extracurricular sport remains an effective strategy to increase physical activity. However, school sport is often limited to a small number of elite athletes. Few schools provide more inclusive sport programs that offer a wider array of activities regardless of ability. Purpose The aim of this study was to examine school sport participation in middle schools (ages 11-14) with contrasting school sport delivery strategies (intramural vs. interscholastic). Methods Data were obtained throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 42 publications
3
53
2
3
Order By: Relevance
“…In addition, since the research group has worked in a wide range, the literature might have revealed the awareness of participation motivation by age. For example, the study group of Salguera et al [28] consisted of an age range of 8-22; while Gould et al [13] worked with a group at the ages of [8][9][10][11][12][13][14][15][16][17][18][19], and Brodkin and Weiss [6], on the other hand, prefered to make their study on six different age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since the research group has worked in a wide range, the literature might have revealed the awareness of participation motivation by age. For example, the study group of Salguera et al [28] consisted of an age range of 8-22; while Gould et al [13] worked with a group at the ages of [8][9][10][11][12][13][14][15][16][17][18][19], and Brodkin and Weiss [6], on the other hand, prefered to make their study on six different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…[15]). Exercises that can also be called as extracurricular activity are a part and continuation of physical education lessons.…”
Section: Introductionmentioning
confidence: 99%
“…Players from certain socio-economic groups were under-represented in some sports because of economic and neighbourhood differences as well as racial/ethnic tension (Kanters et al, 2012). Young players also encounter challenging experiences which are not always beneficial: they can get hooked up with coaches who are more interested in their own egos than helping young players to grow.…”
Section: Problems Of Sport For Refugee Communitymentioning
confidence: 99%
“…There are many unexplained reasons why women are often excluded in organised sports. Kanters (2012) observed that women from African, American and low-income backgrounds were more likely than their male counterparts to be left out of participating in sports. At some sports clubs, women are treated more harshly and ridiculed by boys and coaches.…”
Section: Gender Division In Sport Sociologymentioning
confidence: 99%
“…In Kanters, [10], it is stated that after school activities are a promising practice to increase spore participation. Some of the questions asked in the studies on individuals participating in recreational activities in national and international literature are why individuals participate in these activities and why they do not participate and what encourages individuals to participate (Kim, et.al.…”
Section: Introductionmentioning
confidence: 99%